Vaccination with the Incidence of Post-Acute Sequelae COVID-19 - Aurelia, Daisy; En Masrika, Nur Upik; Rahman, Ismail (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Post-acute sequelae COVID-19 (PASC) symptoms are present in the vast majority of COVID-19 survivors, even those who have received the COVID-19 vaccine. Until now, vaccines against PASC are still controversial. Some previous findings suggest that vaccines can reduce or worsen PASC symptoms. In addition, there has been no related research in North Maluku Province, especially in Ternate City. This study aims to determine the relationship between vaccine administration and PASC based on the total dose and type of vaccine obtained using a questionnaire-based cross-sectional design questionnaire. The study population was COVID-19 patients diagnosed with RT-PCR or RDT-Ag in 2020–2022, domiciled in Ternate City. The respondents were 133 people. Bivariate analysis showed no effect of vaccine dose administration on the incidence of PASC (P=0.111). Similarly, the type and dose of vaccine based on the did not affect (first dose, P = 1.000), (second dose P = 0.732), and (booster P = 0.434) PASC. In terms of the timing of booster doses, pre- and post-COVID-19, there was no significant effect (P=0.384). However, there was a higher incidence of PASC in responders who received the booster dose post-COVID-19. There is no association between vaccine administration and the incidence of PASC.